Penerapan Metode Weighted Aggregated Sum Product Assessment (WASPAS) dalam Pemilihan Kasir Swalayan Terbaik - Yeni Setiani; Witari Aryunani (STMIK Budi Darma, 2023)
In a supermarket, cashier guards or cashier security have an important role in maintaining the security and comfort of the cashier area. As a retail company, the company gives awards every month to the cashier division as a motivation for them. However, problems arise in performance appraisal because it is too subjective and can be influenced by personal opinion. Therefore, the authors conducted research to create a decision support system (DSS) that can assist in selecting the best cashier with the criteria of appearance, service, discipline, honesty, and responsibility. The method used in this research is Weighted Aggregated Sum Product Assessment (WASPAS), which can solve complex problems effectively by speeding up the decision-making process. With the WASPAS method, problems are grouped based on criteria and weight so that the value of each criterion can be calculated. The results showed that Rozi (A4) was the best alternative with a value of 0.452 and deserved to be the best cashier at a supermarket.